2021
DOI: 10.3389/fimmu.2021.733566
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of B Cell Aging in Health and Disease

Abstract: Aging is considered to be an important risk factor for several inflammatory diseases. B cells play a major role in chronic inflammatory diseases by antibody secretion, antigen presentation and T cell regulation. Different B cell subsets have been implicated in infections and multiple autoimmune diseases. Since aging decreases B cell numbers, affects B cell subsets and impairs antibody responses, the aged B cell is expected to have major impacts on the development and progression of these diseases. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 245 publications
1
22
0
1
Order By: Relevance
“…Breg cells are now widely accepted as important regulatory components of the immune system. They provide the host with immune tolerance and immunomodulatory functions, which can be mediated by the production of anti-inflammatory cytokines, such as IL-10, IL-35, and TGF-β, and ensuing suppression of T cells ( Wang et al, 2020b ; de Mol et al, 2021 ). It has been shown that B lymphocytopenia with the appearance of Bregs is the earliest event, likely leading to immunoparalysis in sepsis ( Umakoshi et al, 2020 ).…”
Section: The Key Role Of B Cells In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Breg cells are now widely accepted as important regulatory components of the immune system. They provide the host with immune tolerance and immunomodulatory functions, which can be mediated by the production of anti-inflammatory cytokines, such as IL-10, IL-35, and TGF-β, and ensuing suppression of T cells ( Wang et al, 2020b ; de Mol et al, 2021 ). It has been shown that B lymphocytopenia with the appearance of Bregs is the earliest event, likely leading to immunoparalysis in sepsis ( Umakoshi et al, 2020 ).…”
Section: The Key Role Of B Cells In Sepsismentioning
confidence: 99%
“…Given that decreased B cell numbers and dysfunction are common in sepsis and are associated with poor outcomes, restoring B cell numbers and/or function and maintaining a normal peripheral B-lymphocyte pool in sepsis may help improve the outcomes ( Figure 4 ). HSCs rejuvenation therapies, such as FOXOs and CASIN, can modulate cell survival and growth, increase the common lymphoid progenitor pool, and restore B-cell numbers ( Akunuru and Geiger, 2016 ; de Mol et al, 2021 ). It could be inferred that similar HSC rejuvenation therapies and drugs may be an interesting therapeutic strategy to restore the reduced B-cell numbers in sepsis.…”
Section: Clinical Applications and Therapeutic Potential Of B Cells I...mentioning
confidence: 99%
“…B cells, a subset of adaptive immune cells, are crucially important in both cellular immunity and humoral immunity through secretion of antibodies, presentation of antigens and regulation of T cell functions ( 125 ). In addition to alterations in HSCs, intermediate and mature stages of B cell development also show a series of aging-associated changes.…”
Section: The Alterations Of Immune Cell Subsets Related To Immunosene...mentioning
confidence: 99%
“…Es finden sich Veränderungen bei der Diversität der Antikörper, was auf eine veränderte somatische Rekombination und eine reduzierte somatische Hypermutation („junctional diversity“) zurückzuführen sein könnte. Parallel wurden eine reduzierte Affinität und Neutralisierungskapazität der Antikörper, eine erhöhte Sekretion von proinflammatorischen Zytokinen und ein erhöhtes Vorkommen von Autoantikörpern nachgewiesen [ 21 ].…”
Section: Funktionalität Und Veränderungen Mit Dem Alterunclassified